Política pública de transferência direta de renda e voto para governador: o caso do Programa Renda Cidadã em Goiás - Morais, Marina Almeida (2021)
The present work investigates the role of a public policy - the Citizen Income Program (PRC) - in the choice of vote for governor of Goiás in the 2014 and 2018 elections, with wealth and vertical partisan alignment as competing variables. The unit of analysis is the municipalities and the data sources are the Regional Electoral Court of Goiás and indicators of the Municipality Performance Index (IDM), prepared by the Mauro Borges Institute. Specifically, the hypothesis is that the scenario in which the municipalities with the highest percentage of families served by the PRC are those that present the highest percentage of votes for the situationist candidates. Concurrently, there are the hypotheses that the greater the wealth of the municipalities and the existence of a mayor whose party affiliation is aligned with the governor leads to greater chances of voting for the situationist candidate. The results don’t allow to infer that any of the variables show explanatory power over the phonomenon, although it was possible to identify statistic significant low baselines between being benefited by the PRC and voting on the incumbent.